Treatment of eating disorders: A systematic meta-review of meta-analyses and network meta-analyses - Monteleone, Alessio Maria; Pellegrino, Francesca; Croatto, Giovanni; Carfagno, Marco; Hilbert, Anja; Treasure, Janet; Wade, Tracey; Bulik, Cynthia M.; Zipfel, Stephan; Hay, Phillipa; Schmidt, Ulrike; Castellini, Giovanni; et al. (Neuroscience and biobehavioral reviews, 2022)
MONTELEONE, A.M., F. Pellegrino, G. Croatto, M. Carfagno, A. Hilbert, J. Treasure, T. Wade, C. Bulik, S. Zipfel, P. Hay, U. Schmidt, G. Castellini, A. Favaro, F. Fernandez-Aranda, J. Il Shin, U. Voderholzer, V. Ricca, D. Moretti, D. Busatta, G. Abbate-Daga, F. Ciullini, G. Cascino, F. Monaco, C.U. Correll and M. Solmi. Treatment of Eating Disorders: a systematic meta-review of meta-analyses and network meta-analyses. NEUROSCI BIOBEHAV REV 21(1) XXX-XXX, 2022.- Treatment efficacy for eating disorders (EDs) is modest and guidelines differ. We summarized findings/quality of (network) meta-analyses (N)MA of randomized controlled trials (RCTs) in EDs. Systematic meta-review ((N)MA of RCTs, ED, active/inactive control), using (anorexia or bulimia or eating disorder) AND (meta-analy*) in PubMed/PsycINFO/Cochrane database up to December 15th, 2020. Standardized mean difference, odds/risk ratio vs control were summarized at end of treatment and follow-up. Interventions involving family (family-based therapy, FBT) outperformed active control in adults/adolescents with anorexia nervosa (AN), and in adolescents with bulimia nervosa (BN). In adults with BN, individual cognitive behavioural therapy (CBT)-ED had the broadest efficacy versus active control; also, antidepressants outperformed active. In mixed age groups with binge-eating disorder (BED), psychotherapy, and lisdexamfetamine outperformed active control. Antidepressants, stimulants outperformed placebo, despite lower acceptability, as did CBT-ED versus waitlist/no treatment. Family-based therapy is effective in AN and BN (adolescents). CBT-ED has the largest efficacy in BN (adults), followed by antidepressants, as well as psychotherapy in BED (mixed). Medications have short-term efficacy in BED (adults). •Family interventions were the most effective in anorexia nervosa, proving also beneficial in adolescents with bulimia nervosa.•In adults with bulimia nervosa, cognitive behavioural therapy showed the broadest efficacy, followed by antidepressants.•For binge eating disorder, psychotherapy was beneficial, as well as antidepressants and stimulants.•There is urgent need of novel treatments particularly in anorexia nervosa.